A Study on Ergonomics for Employee Wellness (International Journal of Innovative Research in Computer Science & Technology, 2020)
The nature of work in modern society is  changing rapidly, and competition in the job market is  getting more intense. This requires competence from  workers and demands them to update their knowledge,  skills, and attitudes in order to remain productive and  retain their attractiveness in the job market. On the other  hand, skilful employees are a company’s most important  competitive assets, and so it is worth to up- skill the  employees by providing training at regular intervals on  process and also on governing themselves from  workplace illness. Thus the present study is an attempt to  create awareness on ergonomics that impact employee  performance. The significance and prominent role of  ergonomics is reviewed by discussing its association with  other scientific disciplines and by ascribing types of  ergonomics and its principles and applications towards  employee wellness.
Keywords: Ergonomics; physical; Cognitive; Organisational ergonomics; Human; Machine; Environment; Types of ergonomics; ergonomic disciplines